Reclaiming Female Agency through Écriture Féminine in Carol Ann Duffy’s The World’s Wife - Fauziah Rahmalia, Salma; Assiddiqi, Hasbi; Nurrachman, Dian (Lembaga Teewan Journal Solutions, 2026)
This study examines the textual strategies used to reclaim female agency in Carol Ann Duffy’s poetry collection “The World’s Wife” through Hélène Cixous’s framework of écriture féminine. While past research heavily generalizes historical or mythological adaptations, this paper addresses a critical gap by analyzing the exact linguistic subversion and structural reconstruction of the female body and voice. Applying a mimetic approach and qualitative close reading, this study analyzes three specific poems: